Pain-induced changes in cervical muscle activation do not affect muscle fatigability during sustained isometric contraction - Falla, Deborah; Farina, Dario; Kanstrup Dahl, Marlene; Graven-Nielsen, Thomas (Journal of electromyography and kinesiology, 2008)
This study investigated whether pain-induced changes in cervical muscle activation affect myoelectric manifestations of cervical muscle fatigue. Surface EMG signals were detected from the sternocleidomastoid and splenius capitis muscles bilaterally from 14 healthy subjects during 20-s cervical flexion contractions at 25% of the maximal force. Measurements were performed before and after the injection of 0.5 ml of hypertonic (painful) or isotonic (control) saline into either the sternocleidomastoid or splenius capitis in two experimental sessions. EMG average rectified value and mean power spectral frequency were estimated throughout the sustained contraction. Sternocleidomastoid or splenius capitis muscle pain resulted in lower sternocleidomastoid EMG average rectified value on the side of pain ( P < 0.01). However, changes over time of sternocleidomastoid EMG average rectified value and mean frequency (myoelectric manifestations of fatigue) during sustained flexion were not changed during muscle pain. These results demonstrate that pain-induced modifications of cervical muscle activity do not change myoelectric manifestations of fatigue. This finding has implications for interpreting the mechanisms underlying greater cervical muscle fatigue in people with neck pain disorders.